2008
DOI: 10.3176/earth.2008.1.01
|View full text |Cite
|
Sign up to set email alerts
|

The regional stratotype section and point for the base of the Hirnantian Stage (the uppermost Ordovician) at Mirny Creek, Omulev Mountains, Northeast Russia

Abstract: A complete Hirnantian sequence comprising the Normalograptus extraordinarius and N. persculptus biozones is well developed at the Mirny Creek section in the Omulev Mountains. The underlying beds are assigned to the Appendispinograptus supernus Biozone, and in the overlying strata the lower boundary of the Silurian is precisely defined at the base of the Akidograptus ascensus Biozone. Due to the completeness of the sedimentary and palaeontological record, the Mirny Creek section can be considered as a reference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 13 publications
0
25
0
Order By: Relevance
“…The sedimentary strata are partly strongly folded and faulted, some intervals are covered and some contacts are tectonic (Oradovskaya & Sobolevskaya 1979). Still, the primary authors cited above and Koren′ & Sobolevskaya (2008) showed that the succession of the study interval is not seriously disturbed at key levels and is biostratigraphically continuous. The conodont colour alteration index indicates (Nowlan & Barnes 1987) that the rocks are thermally altered.…”
Section: Mirnymentioning
confidence: 95%
See 2 more Smart Citations
“…The sedimentary strata are partly strongly folded and faulted, some intervals are covered and some contacts are tectonic (Oradovskaya & Sobolevskaya 1979). Still, the primary authors cited above and Koren′ & Sobolevskaya (2008) showed that the succession of the study interval is not seriously disturbed at key levels and is biostratigraphically continuous. The conodont colour alteration index indicates (Nowlan & Barnes 1987) that the rocks are thermally altered.…”
Section: Mirnymentioning
confidence: 95%
“…Chitinozoans, except rare poorly preserved fragments, were not found. Shelly fossils like brachiopods and trilobites are quite common at some levels, but graptolites play a leading role in biostratigraphy and are used for the establishment of a clear general biozonal framework of the Mirny section (Koren′ & Sobolevskaya 2008). Despite the occurrence of mixed shelly-graptolite assemblages in the studied section, detailed correlation with shelly faunal successions in the Baltic and some other regions is problematic due to scarcity of microfossils.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Only a single occurrence of a diplograptine taxon, Paraorthograptus cf. pacificus, was found in the lowest Hirnantian strata (Koren' & Sobolevskaya 2008). On the other hand, Normalograptus ojsuensis is restricted to strata of the uppermost pacificus Subzone.…”
Section: Correlationmentioning
confidence: 98%
“…-In the Mirny Creek region (Omulev Mountains) of NE Siberia Koren' et al (1983) recognized the Appendispinograptus longispinus and Paraorthograptus pacificus subzones within upper Katian A. supernus Biozone. The biostratigraphy of the uppermost Katian to lowest Rhuddanian part of the succession was updated and slightly revised by Koren' & Sobolevskaya (2008). Only eight sample levels were reported in the supernus Biozone at Mirny Creek (only two in the lower subzone), which does not allow for high resolution correlation.…”
Section: Correlationmentioning
confidence: 99%